1999
DOI: 10.1021/bc9801530
|View full text |Cite
|
Sign up to set email alerts
|

Caged DNA Does Not Aggregate in High Ionic Strength Solutions

Abstract: The assembly of DNA into compact particles that do not aggregate in physiologic salt solution occurs naturally in chromatin and viral particles but has been challenging to duplicate using artificial constructs. Cross-linking amino-containing polycations in the presence of DNA with bisimidoester cross-linker leads to the formation of caged DNA particles that are stable in salt solutions. This first demonstration of caged DNA provides insight into how natural condensation processes avoid aggregation and a promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…The authors, however, concluded that the crosslinked complexes lost their transfection activity and proposed therefore that it was necessary to use less stable disulfide linkage; notably the study included no microinjection component, so intracytoplasmic reduction could not be assessed directly. 6 In summary, this study shows that the apparently contradictory demands for successful systemic administration and efficient gene expression of nonviral gene delivery vectors can be addressed by design of complexes for activation by appropriate trigger mechanisms. Application of reduction-cleavable surface crosslinking provides extracellular stability, with extended plasma circulation times, coupled with efficient transgene expression following entry into target cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors, however, concluded that the crosslinked complexes lost their transfection activity and proposed therefore that it was necessary to use less stable disulfide linkage; notably the study included no microinjection component, so intracytoplasmic reduction could not be assessed directly. 6 In summary, this study shows that the apparently contradictory demands for successful systemic administration and efficient gene expression of nonviral gene delivery vectors can be addressed by design of complexes for activation by appropriate trigger mechanisms. Application of reduction-cleavable surface crosslinking provides extracellular stability, with extended plasma circulation times, coupled with efficient transgene expression following entry into target cells.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, it was reported that crosslinked PLL/DNA complexes were less prone to saltinduced aggregation. 6 We therefore examined aggregation of PLL/DNA complexes in 0.15 m NaCl, but no significant effect of crosslinking was observed and both the crosslinked and non-crosslinked complexes aggre-gated extensively over 30 min, reaching sizes of ෂ1 m (data not shown). Fortunately, methods are available to increase the solubility of such PLL/DNA complexes, including surface modification of the complexes with PEG or other hydrophilic polymers.…”
Section: Figure 4 Transmission Electron Microscopy Of Dna Complexes mentioning
confidence: 99%
“…However, the slow reversal of the Schiff bases resulted in limited in vitro and in vivo gene expression. Other reversible cross-linking agents have also been applied to form caged DNA condensates (20) by template polymerization (21), but thus far they have not been shown to be transfection competent.…”
mentioning
confidence: 99%
“…15,30,31,34 The ability to control the metabolic half-life of DNA co-condensates by changing the glutaraldehyde cross-linking level is a unique feature of this DNA formulation. The mechanism by which glutaraldehyde cross-linking delays DNA metabolism is most likely related to either caging of the DNA to protect it from DNase 35 or chemical masking of the peptide backbone of PEG-CWK 18 and Man9-CWK 18 from proteases by derivatization of the lysine side chains. 23 The results presented in Figure 4 indicate that increasing the glutaraldehyde cross-linking from 6 to 15 equiv nearly doubles the t 1/2 from 3.7 to 6 h and similarly in¯uences the level of transient gene expression ( Figures 6A, versus 6C).…”
Section: Discussionmentioning
confidence: 99%